(untitled) (Research, Society and Development, 2022)
Cocoa (theobroma cacao), is an economically important crop in several tropical countries. In brazil, the cocoa agroindustry occupies a place of expression in the north and northeast regions, which stands out among those used in seed production, as they are used as raw material for chocolate manufacturing, and the pulp of these fruits is little used in the food industry. The cajá (spondias mombin), has wide tropical distribution, this fruit is, today, cultivated in the north and northeast regions, and can also be known as taperebá, is of flavor, aroma and color suitable for the conquest of the most demanding palates. The objective of this study was to evaluate the commercial stability (shelf life) of the alcoholic fermented beverage of cocoa and cajá pulps, of the following experimental formunation called, fa2 (40% cocoa 60% cajá), where chemical physical attributes of: ph, volatile acidity, fixed acidity, vitamin c, total sugars, reducing sugar and alcohol content, lasting a period of 90 days were evaluated. The results remained stable in the period of commercial stability analyses (shelf life), and significant reductions were observed, more than small, in the physical chemical parameters analyzed at time zero (0) at 90 days, shown by the means and standard deviation (n=3), and by the tukey test at 5% (p≤0.05). The alcoholic fermented fa2 (40% cocoa and 60% cajá) showed to be a great economic and nutritional potential for the regions of the cerrado tocantinense and sul pará region, contributing to the generation of income of these communities and adding value to the commercialized product.